Valoración de empresa: Cajas Colombianas SAS (2024)
Cajas Colombianas is a Valle del Cauca-based company with over 54 years in the cardboard packaging and containers market, serving corporate clients such as Bavaria, Nestlé, Colombina, and Cristar Tabletop. It is part of a business group founded by Alberto Carbonari and his family, currently undergoing a succession process to the third generation. The objective of this report is to determine the economic value of Cajas Colombianas for the year 2024. The valuation was conducted using the discounted cash flow method, going concern value, and multiples. The report includes an analysis of the internal and external context, as well as a financial analysis of the company compared to the industry. The main challenges for Cajascol are to improve its cash conversion cycle, primarily through inventory turnover, to implement strategies to reduce the cost of raw materials, and to enhance operational efficiency. To achieve this, it relies on the strength of three generations working together, a market with high growth potential and sustainability, as well as a highly experienced and skilled workforce. After calculating the company's value, a sensitivity analysis was performed to assess the internal and external risks faced by Cajascol. The results indicate that the enterprise value of Cajas Colombianas ranges from $20,688 million to $30,328 million pesos. By weighting the valuation methods, an average weighted value of $28,017 million pesos was established. Keywords: Valuation, discounted cash flow, going concern value, financial analysis, sensitivity analysis, enterprise value.